Statistični pristop k analizi hladilnih sistemov s hladilnimi stolpi na naravni vlek - Smrekar, Jure (Strojniški vestnik, 2005)
Changes to the operating requirements at power plants, with the intention of lowering energy costs and ensuring a cleaner environment, have brought optimization to the whole process. In principle, the process consists of an inlet heat stream to the process, the steam cycle itself and the rejected heatstream to the environment. The optimization of all three parts of the energetic system will ensure the best results. This study relates to an analysis of the measurements of energetic parameters at Block 4 of the Sostanjpower plant and shows the influence of the cooling system on the power plantćs efficiency. The paper includes a statistical approach to the analysis of a thermo-energetic system that enables an understanding of the relations between the parameters and shows guidelines for enlarging the thermo-energeticefficiency. The main part of the cooling system is the natural-draft cooling tower, which represents the interaction between the power plant and the environment. Approaching the optimal operating point of the cooling system contributes to fuel savings and decreasing the amount of exhaust-gas pollution. This paper also includes a verification of the typical linear relation between the heat transferred to the environment and the generation of power.
Keywords: sistemi hladilni; stolpi hladilni; analize sistemov; postopki statistični; hladilni sistemi; hladilni stolpi; termoelektrarne